Background - Tan, R.; Leong, J.; Sidhu, Amandeep (2018)
© Springer International Publishing AG 2018. When measuring large data volumes and computations, working in the region of petabytes and petaflops is considered working in petascale (1015). Supercomputers achieved the feat of being able to compute at a petaflop in 2007, as listed in the Top500 List which ranks and keeps track of the 500 fastest computers annually [45].